Airman and Family Resilience Lessons from the Scientific Literature - Meadows, Sarah O. (RAND Corporation, 2015)
This final report in a series is designed to help the Air Force promote mental and physical resilience among its Airmen, civilian employees, and Air Force families and thus improve overall health and well-being. The report reviews the concepts and measures of resilience, resilience factors, hardiness and flourishing. It highlights the eight fitness domain companion reports and types of Air Force data that could be used to track resilience.